CONTINUOUS IMPROVEMENT IN THE UNIVERSITY TEACHING:THE TEM MODEL - Verna, Ida; Lucianetti, Lorenzo (European Scientific Journal, ESJ, 2014)
The developed research suggests an experimental model for the evaluation of university teaching: the Teaching Evaluation Model (TEM) based on principles and methods of quality. This latter choice as objective of the developed work (continuous improvement of the quality of teaching), and therefore as a "method of operation" (the Deming Cycle). The application of the TEM model takes place in 4 stages: lesson planning (plan), implementing (do), student learning assessment (check 1), teacher self-assessment (check 2), definition and implementation of corrective actions. Continuous improvement of each lesson and quality improvement of a university course represents the main outcome of the TEM model.